2017
DOI: 10.1093/molbev/msx054
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Highly Divergent Diatom-Derived Chloroplasts in Dinoflagellates, Including a Description of Durinskia kwazulunatalensis sp. nov. (Peridiniales, Dinophyceae)

Abstract: Dinoflagellates are known to possess chloroplasts of multiple origins derived from a red alga, a green alga, haptophytes, or diatoms. The monophyletic "dinotoms" harbor a chloroplast of diatom origin, but their chloroplasts are polyphyletic belonging to one of four genera: Chaetoceros, Cyclotella, Discostella, or Nitzschia. It has been speculated that serial replacement of diatom-derived chloroplasts by other diatoms has caused this diversity of chloroplasts. Although previous work suggested that the endosymbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 42 publications
(85 reference statements)
1
49
0
Order By: Relevance
“…The diatom that became the endosymbiont of the D. baltica (strain CSIRO CS‐38) is most closely related to the N. palea strain Spain C according to a phylogeny created by Yamada et al. () using the chloroplast rbc L marker. This is confirmed in the plastome and chondriome single gene phylogenies presented in this paper (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The diatom that became the endosymbiont of the D. baltica (strain CSIRO CS‐38) is most closely related to the N. palea strain Spain C according to a phylogeny created by Yamada et al. () using the chloroplast rbc L marker. This is confirmed in the plastome and chondriome single gene phylogenies presented in this paper (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indirect evidence that Nitzschia may have been the diatom genus incorporated into Durinskia was also noted by the presence of plastid plasmids in both genera (Imanian et al 2010). Most recently, Yamada et al (2017) analyzed rbcL and SSU rDNA sequences from 14 dinotoms and demonstrated a phylogenetic relationship of six marine dinotom endosymbionts to different Nitzschia species, showing this relationship has been initiated numerous times, independently. Several of the endosymbionts were resolved to the species level, including the dinotom D. baltica (strain CSIRO CS-38) which grouped with the Nitzschia palea strain "SpainC."…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…One possibility would be a serial endosymbiosis event deep in haptophyte evolutionary history, in which an ancient plastid derived from a pelagophyte/dictyochophyte ancestor was acquired by the haptophyte common ancestor, then replaced subsequently by a plastid of non-ochrophyte origin (Figure 10—figure supplement 2). This discrepancy, alongside others such as the presence of green algal genes in ochrophytes, bolsters the possibility that serial plastid endosymbiosis has been a widespread component of the evolution of CASH lineage plastids other than the dinoflagellates, in which it is a well established phenomenon (Dorrell and Howe, 2015; Yamada et al, 2017). Verifying this scenario, or its alternatives (such as lateral gene transfer from pelagophyte or dictyochophyte algae into the algal ancestors of the haptophyte plastid) rests on identifying the exact origin of the current haptophyte plastid genome, and in particular demonstrating that the haptophyte plastid genome originates from within (rather than forms a sister-group to) a major lineage of eukaryotic algae other than ochrophytes (Figure 10—figure supplement 2).…”
Section: Discussionmentioning
confidence: 99%